Impact of Geopolitical Tension on the World Economy and the Economy of Kazakhstan (International relations and international law Journal, 2023)
This article attempts to assess the impact of geopolitical tension on the world economy, trade, including the Kazakh economy.Geopolitical tensions hit the global economy when the recovery from the COVID-19 pandemic was underway, and strong inflationary pressures had already emerged. The consequences of this tension affect the economies of countries around the world. First, the impact affects commodity prices. Secondly, trade flows have been destabilized, the supply chain has been disrupted, and there are serious consequences for the countries of the Caucasus, Central Asia, Eastern Europe and the Baltic States, as well as other countries. Thirdly, as a result of the weakening of the economies of many countries, financial conditions have tightened. Due to the increase in prices for energy, goods and food, global inflation intensified in many countries. The volume of global trade in goods and services decreased by 3.4 percent from October 2021 to October 2022, which means a global trade deficit of about $1 trillion per a year. Energy prices have risen by about 100 percent, while non-energy prices have risen by only 8 percent on average. As a result, there is a danger that the world economy may be divided into separate economic blocs with different ideologies, political systems, technological standards, systems of cross-border payments and trade and reserve currencies.Key words: geopolitical tension, risks, contradictions, economy, trade, Kazakhstan.